The effects of age, glucose ingestion and gluco-regulatory control on episodic memory - Riby, Leigh Martin; Meikle, Andrew; Glover, Cheryl (Age and ageing, 2004)
Background: previous research has been inconclusive regarding the impact of glucose ingestion and gluco-regulatory control on cognitive performance in healthy older adults. The aim of this research was to determine whether glucose specifically enhanced episodic memory in an older population. In addition, the link between individual differences in glucose regulation and the magnitude of the enhancement effect was examined. Design and subjects: a within subjects, counterbalanced, crossover design was used with 20 participants (60–80 year olds), each serving as his/her control. Methods: episodic memory was tested by presenting unrelated paired associates followed by immediate and delayed cued recall, and delayed recognition, under single and dual task conditions. In addition, a battery of cognitive tests was administered, including tests of semantic memory, working memory and speed of processing. Results: glucose ingestion was found to largely facilitate performance of episodic memory. Furthermore, subsidiary analyses found that gluco-regulatory efficiency predicted episodic memory performance in both control and glucose conditions. Conclusions: a boost in performance after glucose ingestion was particularly seen in the episodic memory domain. Notably, strong evidence was provided for the utility of gluco-regulatory control measures as indicators of cognitive decline in the elderly.